Mengubah Arah Ekonomi Nasional: Potensi Ekonomi Syariah yang Tak Terbendung - Meirani Rahayu Rukmanda; Nurhadi, Nurhadi; Dewi Retna Wulan (Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
The potential of the sharia economy in Indonesia, with a majority Muslim population, has a great opportunity to become the main driver of national economic growth. This study aims to analyze the main factors that drive the growth of the sharia economy, including government policies, public awareness, and adaptation of digital technology. Through qualitative research methods based on literature studies, it was found that strengthening regulations, technology-based product innovation, and sharia-based financial inclusion are key elements in building a sustainable sharia economic ecosystem. The government has a strategic role through policies such as the establishment of KNEKS, the merger of state-owned sharia banks, and the implementation of the Sharia KUR program. Although there are challenges such as limited infrastructure and low coordination between agencies, the implementation of the right strategy can optimize the potential of this sector. The results of the study show that collaboration between the financial sector, small and medium enterprises (SMEs), and the government is able to encourage the competitiveness of the Indonesian sharia economy at the global level, while contributing to an inclusive and sustainable national economic transformation.